STUDI KOMPARATIF PENDAPATAN, BIAYA DAN KELAYAKAN USAHA AGROINDUSTRI GULA SEMUT PADA SETIAP PELAKU RANTAI PEMASARAN - Dindy Darmawati Putri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This study aims to determine the comparative analysis of income, costs, and feasibility analysis of agro-industry in brown sugar agro-industry marketing chain in the Special Region of Yogyakarta. The research method used a descriptive analysis method. This research was conducted in Girimulyo and Kokap Districts as brown sugar production centers. The method of data collection is done by survey technique. The method of sampling is simple random sampling consisting of brown sugar crafters, collectors, and Central Processing Unit (CPU) of 60 samples. The results showed that the highest profit was in the Central Processing Unit (CPU), then the collectors, and finally at the level of household-scale brown sugar crafters. This is due to the different business scales, limited capital, and raw materials which become the obstacles of the craftsmen in developing their businesses. While seen from the feasibility of the RC ratio, all RC ratios> 1 means that all businesses in the marketing chain are feasible.